Activated Hepatic Stellate Cells in Hepatocellular Carcinoma: Their Role as a Potential Target for Future Therapies - Ali, Esraa; Trailin, Andriy; Ambrozkiewicz, Filip; Liška, Václav; Hemminki, Kari (International journal of molecular sciences, 2022)
Hepatocellular carcinoma (HCC) is a global healthcare challenge, which affects more than 815,000 new cases every year. Activated hepatic stellate cells (aHSCs) remain the principal cells that drive HCC onset and growth. aHSCs suppress the anti-tumor immune response through interaction with different immune cells. They also increase the deposition of the extracellular matrix proteins, challenging the reversion of fibrosis and increasing HCC growth and metastasis. Therapy for HCC was reported to activate HSCs, which could explain the low efficacy of current treatments. Conversely, recent studies aimed at the deactivation of HSCs show that they have been able to inhibit HCC growth. In this review article, we discuss the role of aHSCs in HCC pathophysiology and therapy. Finally, we provide suggestions for the experimental implementation of HSCs in HCC therapies.
Keywords: pohyb buněk; hepatocelulární karcinom; fibrosis regression; Cell Movement; hepatocellular carcinoma; hepatic stellate cells; Carcinoma, Hepatocellular; jaterní hvězdicovité buňky; Hepatic Stellate Cells; therapeutic studies; nádorové buněčné linie; lidé; Liver Neoplasms; nádory jater; Cell Line, Tumor; Humans